Community-led Priority Setting for Opioid Use Disorder in Pregnancy and Parenting. Issue 5 (September 2021) - Altman, Molly R.; Busse, Morgan; Kim, Jane; Ervin, Ayla; Unite, Marianne; Kantrowitz-Gordon, Ira
Abstract : Objectives: To engage community members with opioid use disorder (OUD) and case managers working with pregnant and parenting individuals with OUD in a priority setting process to identify the key priorities for research, policy, and care improvement during pregnancy, birth, and postpartum. Methods: We conducted focus groups across Washington State with pregnant and parenting people with OUD and with case managers working with this community as part of research priority setting using the validated Research Prioritization by Affected Communities protocol. Priorities for research, policy, and service improvement were developed during each focus group by the participants. Results: Three focus groups with pregnant and parenting people with OUD and 2 focus groups with case managers were conducted (total N = 24 and 16, respectively). Both prioritized topics such as stigma and bias, housing, access to treatment, and steps toward successful recovery. The community and case manager groups shared similar, complementary strategies for each priority, with differences reflecting their perspectives in relation to OUD. Conclusions: Community-engaged priority setting among those with OUD was an effective and meaningful way to guide future research, policy, and care improvement efforts.